Mink SLAM V-Region V74I Substitutions Contribute to the Formation of Syncytia Induced by Canine Distemper Virus - Wang, Yawen; Chen, Jie; Hu, Bo; Gong, Chengyan; Shi, Ning; Liu, Mengjia; Yan, Xijun; Bai, Xue; Zhao, Jianjun (Frontiers in Veterinary Science, 2021)
Amino acid differences in the signaling lymphocyte activation molecules (SLAM or CD150) variable (V) region affect the interaction between SLAM and the canine distemper virus (CDV) hemagglutinin (H) protein and may be responsible for the level of susceptibility or resistance of a species to CDV. Here, using the raccoon dog SLAM (rSLAM) and mink SLAM (mSLAM), we performed SLAM-V homologous modeling, site-directed mutagenesis and surface expression analysis, as well as a cell fusion assay to study the interaction between SLAM and CDV based on the amino acids at positions 74 and 129 of SLAM. Our results indicated that residues 74 and 129 of SLAM are both located in the interface region interacting with CDV H, and that amino acid substitutions at these positions have a slight effect on the expression of SLAM. The SLAM-V74I and SLAM-R129Q mutations in mink significantly improved cell fusion efficiency of CDV. In contrast, SLAM-I74V or SLAM-Q129R mutation in raccoon dog significantly decreased cell fusion efficiency. We conclude that SLAM amino acids 74 and 129 play an important role in cell fusion efficiency.